Pemanfaatan Karbon Baggase Teraktivasi Untuk Menurunkan Kadar Logam Tembaga Pada Limbah Kerajinan Perak Di Lombok Tengah - Indah, Dahlia Rosma; Safnowandi, Safnowandi (Hydrogen: Jurnal Kependidikan Kimia, 2019)
Copper metal levels in silver craft waste can cause health problems in humans and pollute the surrounding environment. One method of processing wastewater is the adsorption technique using activated carbon dioxide. The first step is to first determine the copper metal content in silver handicraft waste in Ungga Village, Central Lombok. Furthermore, the waste water is contacted with activated carbon. The production of activated bagasse carbon consists of three stages, namely first dehydration by burning bagasse until it turns into carbon, second carbonation which is heating temperature of 500ºC, carbon yields of 100- 200 mesh and third, activation by immersing 50 grams of carbon in 500 mL 15% NaOH during 12 hours. After that the carbon is dried at 110ºC and finally heated at 500ºC for 1 hour. The bagasse carbon that has been made is put into 25 mL of waste water sample with a mass of 2 grams of adsorbent. The sample is then stirred at various contact times of 30, 60, 90, 120 and 150 minutes at a speed of 180 rpm using a batch system. The optimum contact time and concentration are used to calculate the efficiency of decreasing copper metal content by calculating the difference in copper metal content before adsorption and after adsorption using activated carbon dioxide. The concentration of all Cu (II) metals was analyzed using Atomic Absorption Spectrophotometer (AAS). From the research it was found that the copper metal content in the sample was 14.5710 ppm. The optimum contact time for copper metal adsorption is at 120 minutes contact time which results in optimum adsorption efficiency in ferrous metals, namely 84.88%.